Usability Testing of ITTS MART v2.0 through Customer Satisfaction Index (CSI) Measurement using the E-SERVQUAL Model - Zunaidi, Rizqa Amelia; Yulianita, Ika; Putra, Perdana Suteja; Mardhiana, Hawwin (Sistemasi: Jurnal Sistem Informasi, 2024)
The current advancement in information technology brings convenience to users, especially in accessing the internet, including through mobile devices like smartphones. The rapid growth in internet usage, particularly via mobile devices, is driven by the popularity of social media applications as virtual social interaction platforms. In addition to being a means of social interaction, social media also serves as a promotional platform, including for online shopping applications, contributing to the increase in online shopping transactions in Indonesia. At the Telkom University Institute of Technology in Surabaya, hydroponic and aquaponic activities have seen significant development and have reached the stage of product harvesting. Therefore, a platform is needed to market these products. The decision has been made to utilize an online grocery shopping platform, primarily through a mobile application, to enable consumers to make purchases anytime and anywhere they are. The online grocery shopping platform being developed by ITTelkom Surabaya is known as ITTS MART. Currently, ITTS MART is still in the prototype development stage and requires usability testing by measuring the Customer Satisfaction Index (CSI) using the e-SERVQUAL model. The results of this study indicate that the Customer Satisfaction Index (CSI) for the ITTS MART application service is 86.20%, signifying that users of the ITTS MART application are highly satisfied with its service. Although the CSI score for the ITTS MART application is already very good, users still express some dissatisfaction with variables such as system availability, privacy, and responsiveness. This is particularly noticeable in indicators like the frequency of application availability for business, obtaining permission before creating a personal account, safeguarding privacy, and accuracy of product descriptions within the application. Therefore, developers of the ITTS MART application should work on improving these aspects to enhance user satisfaction with the application.